SYNTHESIS AND CHARACTERIZATION OF NOVEL SIDE-CHAIN NONLINEAR-OPTICAL POLYMERS BASED ON POLY(1,6-HEPTADIYNE) DERIVATIVES - LEE, HJ; KANG, SJ; KIM, HK; CHO, HN; PARK, JT; CHOI, SK (AMER CHEMICAL SOC, 1995)
Novel types of multifunctional polymer that contain a conjugated backbone for both third- and second-order nonlinear optical (NLO) materials have been investigated. We synthesized the 1,6-heptadiyne derivatives bearing NLO chromophores. The resulting monomers were easily homopolymerized and also copolymerized with ethyl dipropargyl(diethoxyphosphoryl)acetate (TDPA) using a metathesis catalyst to give corresponding polymers with large optical nonlinearities. Molecular structural characterizations for the resulting polymers were achieved by H-1- and C-13-NMR, FTIR, and UV-visible spectroscopies. The polymers obtained were found to be amorphous and showed thermal stability up to 250 degrees C. The homogeneous polymer solutions could be spin coated to the optical quality thin films on the ITO glass substrates. These films have been oriented by an electric contact poling process. The electrooptic coefficients, r(33), of the poled polymer films were in the range 1.7-10.1 pm/V, and the nonresonant values of the third-order NLO coefficient, chi((3)), were found to be (2.1-3.3) x 10(-11) esu.
Keywords: LINEAR-POLYMERS; POLYDIACETYLENE; CHROMOPHORES; POLY-4-BCMU; TRANSITION; FILM